Victorian Imperial Infirmities in The Moon Stone: Signs of Failure of Empire - K.C., Chandra Bahadur (Interdisciplinary Journal of Management and Social Sciences, 2021)
Edward Said has the conviction that Victorian novels are complicit to empire. They were the means through which power of British imperialism was continually reinforced and elaborated, but this research does not endorse Said’s view completely. Hence, it goes beyond this conviction and reveals that the Victorian novels do not only support imperial culture; they also expose infirmities of empire. Although Victorian novels share imperial culture and its ethos as Said has shown, they also critique imperial culture. Some novelists of that time struggle to come to terms with the imperial culture. Wilkie Collins is one of them who stages counter narration of resistance to empire in The Moonstone. This veritable narrative text poses questions on the conviction that British Victorian novels are complicit to empire. It criticizes the imperial ambition of Britain and exposes the vulnerabilities of empire. The vulnerabilities are exposed with the bequeathing of the Moonstone by English Colonel Herncastle by murdering the innocent and devoted Brahmins. It is a staunch criticism on corrupt behavior of the colonizers toward material properties of colonized people. It shows that the British colonizers were in India mainly for torturing the colonizers for the sake of their selfish greed. To give justice against such vulnerability, the novelist describes a scene in the ending of the novel in which the Moonstone is restored in its original place in India.